Revision of the subgenus Episyrphus (Episyrphus) Matsumura (Diptera: Syrphidae) in Australia - Wright, Susan G.; Skevington, Jeffrey H. (Zootaxa, 2013)
Three species of Episyrphus (Episyrphus) Matsumura, 1917 are here recorded in Australia: E. (E.) viridaureus (Wiede-mann, 1824) and two new species E. (E.) oliviae Wright sp. nov. and E. (E.) glaber Wright sp. nov. A key to Australian Episyrphus (Episyrphus) species is provided, important taxonomic characters are illustrated and distributions of the three species are mapped. The distribution of E. (E.) viridaureus is extended to include Australia. Mitochondrial cytochrome c oxidase subunit I (COI) data are provided from some Episyrphus species to test morphological species concepts.